2015
DOI: 10.1016/j.jalz.2015.02.013
|View full text |Cite
|
Sign up to set email alerts
|

A 22‐single nucleotide polymorphism Alzheimer's disease risk score correlates with family history, onset age, and cerebrospinal fluid Aβ42

Abstract: The discriminative ability of this 22-SNP GRS is still limited, but these data illustrate that incorporation of age-specific weights improves discriminative ability. GRS-phenotype correlations highlight the feasibility of identifying individuals at highest susceptibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
101
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(113 citation statements)
references
References 27 publications
11
101
1
Order By: Relevance
“…47 48 This 75-year-old limit has been used by us and other studies that combine multiple susceptibility loci into a global genetic risk score to improve the prediction of individuals at risk of suffering AD. 49 There is still an open debate regarding the disclosure of IF to participants participating in imaging studies, since there is still a lack of evidence on which to base practice on the balance of harm versus benefit in telling research participants about findings. 5 The existing literature has evaluated the will of participants in medical and non-medical settings to be informed.…”
Section: Discussionmentioning
confidence: 99%
“…47 48 This 75-year-old limit has been used by us and other studies that combine multiple susceptibility loci into a global genetic risk score to improve the prediction of individuals at risk of suffering AD. 49 There is still an open debate regarding the disclosure of IF to participants participating in imaging studies, since there is still a lack of evidence on which to base practice on the balance of harm versus benefit in telling research participants about findings. 5 The existing literature has evaluated the will of participants in medical and non-medical settings to be informed.…”
Section: Discussionmentioning
confidence: 99%
“…An AD genetic risk score was calculated by multiplying each individual GWAS allele effect size using the beta coefficients obtained from a previous data set. This type of analysis demonstrated that AD genetic risk score could predict LOAD phenotype (Chouraki et al, 2016; Desikan et al, 2017; Sleegers et al, 2015; Verhaaren et al, 2013; Xiao et al, 2015; Yokoyama et al, 2015), mild cognitive impairment conversion to LOAD (Adams et al, 2015; Rodriguez-Rodriguez et al, 2013), hippocampal cortical thickness (Harrison et al, 2016; Sabuncu et al, 2012), hippocampal volume (Lupton et al, 2016), cerebrospinal fluid biomarkers (Martiskainen et al, 2015), and plasma inflammatory biomarkers (Morgan et al, 2017). This approach has been expanded to include further polymorphisms of smaller but important effect sizes to develop a polygenic risk score (PRS) (Euesden et al, 2015).…”
Section: Introductionmentioning
confidence: 96%
“…AD genetic risk scores have been associated with increased risk of late life cognitive impairment [55], AD risk [56], greater risk of conversion from MCI to AD [54,57,58], and discriminating an AD group from controls [59]. Research on genetic risk approaches have used several procedures for calculating risk scores.…”
Section: Introductionmentioning
confidence: 99%